ENTRE LOCUÇÕES E DISCURSOS: DESVENDANDO O FEMINEJO E A REPRESENTAÇÃO DA MULHER EM CANÇÕES SERTANEJAS - PÂMELA DOS SANTOS FUZARO (2025)
Phraseology is a discipline that focuses on the study of phraseological units of languages, that is, the combinations of words frequently used in individuals' everyday communication, which reflect cultural, historical, social, and linguistic aspects (Corpas, 1996). Likewise, sertanejo music, widely popular in Brazil, is deeply connected to the culture and national identity of a community (Napolitano, 2002). Historically, women have faced numerous difficulties in expressing themselves and participating actively in society due to the strong oppression present in past eras, a fact reflected in the male dominance within the sertanejo musical genre. However, with the rise of feminism throughout the 20th century—a movement advocating for women’s rights—women have gained more space and influence in various fields, including the artistic realm. This context has led, for instance, to the emergence of feminejo, a musical subgenre that gives voice to female experiences within the sertanejo scene. Thus, the female representation reflected in songs of this genre requires a dual analysis, guided by phraseological and discursive aspects; that is, an analysis of discourse focused on idiomatic expressions used by both the forerunners and the contemporary artists of the genre, aiming to understand the image of women conveyed in these songs. Therefore, this study aims to investigate the representation of women in feminejo through lexical analysis, focusing on the idiomatic expressions found in the discursive contexts of selected songs. Specifically, the objectives are: to analyze phraseological units in feminejo lyrics as elements that contribute to the construction of women's representation; to investigate possible evolutions in the discourse about women, based on a comparison between pioneer and contemporary feminejo artists; and to evaluate whether the discourses in the songs produce a positive and empowering effect on the representation of women. From a methodological perspective, the analysis considers songs by Marília Mendonça and Maiara & Maraisa, released between 2014 and 2016, as well as songs by Lauana Prado and Yasmin Santos, released between 2020 and 2022. This selection of songs and timeframes represents the development from the emergence to the consolidation of the feminejo genre. In total, 82 songs by the four artists were analyzed. Consequently, in relation to feminist theories, the study discusses the connection between feminejo and feminism, addressing the genre’s evolution as a form of female empowerment. It also examines the role of sertanejo music in the inclusion of women, highlighting artists, recurring themes, and the emergence of the movement. Within the scope of lexical and phraseological studies, the theoretical foundations of the field are presented, considering its evolution, its objects of study, and its relationship with discourse. The study also discusses language as a social practice, linked to identity construction and power dynamics. Based on the analysis, it can be concluded that, although feminejo has advanced in terms of visibility and recognition, the discourses in the songs still do not significantly demonstrate a positive evolution in the representation of women. Keywords: Female representation; Feminejo; Phraseology; Idiomatic expressions; Discourse.